The Impact of Food Safety Management System ISO 22000 on Customer Satisfaction and Loyalty, Case Study of Coca-Cola Company in Algeria - Mekimah Sabri; Sayad Nawel (Economics and Business)
The present paper aims at determining the impact of Food System Management ISO 22000 on Coca-Cola customer’s loyalty in Algeria through satisfaction as an intermediate variable. Based on a descriptive, analytical approach and a case study method, an electronic questionnaire was used as the main tool for data collection. It was distributed to a random sample of 385 customers at Coca Cola Company in Algeria. In addition, SPSS and AMOS programs were used to analyse the data and test the research hypotheses. The paper reached significant conclusions that the level evaluation of ISO 22000, in customers’ point of view, varied between a weak rate of green and safe products, while innovative and quality products were highly rated. The result also demonstrated a weak indirect effect between food safety management system and customer loyalty through satisfaction expressed by a correlation coefficient, which was estimated at 0.23. The direct effect was greater with a correlation coefficient of 0.56. In fact, the output of food safety management system leads directly to the saturation of customer satisfaction and also to loyalty.